ANALYSIS OF MOVIE CLIPS AND STUDENTS’ SELF-CONFIDENCE IN ENGLISH LEARNING - Hermayana, Amelia Resky; Talib, Ahmad; Sally, Fauzan Hari Sudding (Universitas Negeri Makassar, 2025)
This research aims to determine the relationship between movie clips and students’ self-confidence of SMPN 18 Makassar students toward learning English using movie clips. The qualitative method was employed in this study. Students from SMPN 18 Makassar’s class VIII-5 participated in this study during the 2023-2024 school year. Simple random selection was used to choose ten students to participate. An interview is the tool utilized in this study to get information for the research question’s findings Overall, the majority of students gave positive responses to English learning using movie clips. Positive perceptions regarding English learning using movie clips were expressed as follows: 1) Increasing self-confidence, 2) increasing sense of independence, and 3) helping in learning. Therefore, it can be concluded that students have a positive perception of English learning using movie clips.